Snow cover as an indicator of cumulative land pollution - V. R. Alekseev (Лëд и снег, 2015)
A reliable technique has been devised for a simultaneous total and serial retrospective assessment of the ever increasing pollution of lands from aerospace images and from benchmark ground-based observations which permit calculations of the negative human impact on the environment for the particular regions, river drainage basins, states, and for the planet Earth as a whole. Use is made of the glacio-indication approach to the study of polluted territories around cities and transport routes that has come to be known as the «ProcUsmethod». An assessment of the land pollution across the globe was made for 221 administrative entities. Calculations were done for 193 states and 41 trust territories. The total area of polluted lands on the continents was estimated at 13 606 thousand km2 (10% of the Earth’s land surface). The heaviest pollution corresponds to West Europe (44.5% of its area), Micronesia (33.3%), and to the countries within the Caribbean basin (31.1%); the worst levels of land pollution correspond to Australia with New Zealand (2.1%), Melanesia (3.1%), and to Central Africa (3.8%). The most heavily polluted states are China (with the polluted area of 2400 thou km2), India (1460 thou km2), the USA (1156 thou km2), Russia (683 thou km2) and Brazil (657 thou km2).The findings, obtained by the Russian scientists V.G. Prokacheva and V.F. Usachev over the course of the last 30 years, are recognized as a fundamental contribution to glaciology and geoecology. The ProcUs method, suggested by Russian scientists, offers strong possibilities of obtaining quantitative indicators and studying spatiotemporal variability of pollutants. It is recommended that the method should be expanded and sophisticated on the basis of special-purpose ground-truth pilot observations to be used in implementing the Earth’s global ecological monitoring program.